Correction of Length Discrepancy of Radius and Ulna with Distraction Osteogenesis: Three Cases - Kenan Koca; Serkan Akpancar; Cemil Yıldız (Case Reports in Orthopedics)
Objectives. The aim of the study was to investigate the results of patients with isolated length discrepancy between ulna and radius who underwent distraction osteogenesis with unilateral external fixator. Material and Methods. A patient with ulna shortening due to multiple enchondromatosis, a patient with ulna shortening due to ulnar club hand, and a patient with radial shortening due to radial club hand were included in the study. The patients underwent ulna and radial distraction osteogenesis with unilateral external fixator. Range of wrist and forearm motion, deformities, and length discrepancy of ulna and radius were compared at preoperative and postoperative. Results. Duration of external fixation and followup were 2.6 and 23.3 months, respectively. Mean distraction osteogenesis was 1.66 cm. No patient reached the length of normal side. Range of rotation of forearm was increased by 15°. Range of ulnar-radial deviation was increased by 21.6°. Deformity of 15° at patient with multiple enchondromatosis was corrected. Conclusion. Isolated ulna or radius shortening may reduce with distraction osteogenesis by unilateral external fixator to prevent serious deformity.